The contribution of pubertal development to performance scores in high-level rhythmic gymnasts - Tijana Purenović-Ivanović; Ružena Popović; Lidija Moskovljević (Palacký University Olomouc, 2017)
Background: Puberty is a central process in the complex set of changes that constitutes the transition from childhood to adolescence. This period of maturation is characterized by a growth spurt which affects virtually the whole skeleton and muscles and thus affecting children's motor performance. Objective: The present study investigated the role of pubertal status in predicting success in rhythmic gymnasts' (RGs) performance. Methods: One hundred and twenty-six national- and international-level RGs (age: 11.95 ± 3.09 years, body height: 147.76 ± 14.61 cm, body mass: 37.75 ± 11.72 kg, BMI: 16.79 ± 2.26 kg/m2, menarcheal age: 13.57 ± 1.18 years, training experience: 5.88 ± 2.79 years), divided into five age group categories, volunteered to participate in the study. A self-assessment was used for the estimation of the stages of sexual maturity of their breasts and axillary hair development (i.e. Tanner method), whereas the data on RGs menarche were collected by the means of interviewing. Results: Regression analysis showed that axillary hair development was the only independent parameter that had a positive influence on RGs' performance scores (b = 1.693, p = .03, advanced RGs), but overall RGs' pubertal development had a statistically significant influence on their performance [R = .37, R2 = .14, F(3, 122) = 6.475, p < .001], with the explanation of participants' competitive/performance score (Success) in Rhythmic Gymnastics (RG) by 14% of variance. Conclusion: This research indicates that RGs' athletic performance can be predicted by parameters of pubertal development, but not that well (it explains the Success by 14% of variance), and RGs' axillary hair development is a significant predictor of RG performance. In the group of pubertal RGs the established negative relations between the three examined pubertal development parameters and the performance scores could indicate that late maturation is desirable in RG.